2012
DOI: 10.1111/j.1468-1331.2012.03798.x
|View full text |Cite
|
Sign up to set email alerts
|

The PRIPS study: screening battery for subjects at risk for Parkinson's disease

Abstract: With this approach, one out of 16 positively screened participants developed PD compared to one out of 135 in the original cohort. This corresponds to a sensitivity of 80.0%, a specificity of 90.6% and a positive predictive value of 6.1%. These values are higher than for any single screening instrument but still too low for a feasible and cost-effective screening strategy which might require longer follow-up intervals and application of additional instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 22 publications
(50 reference statements)
4
99
0
6
Order By: Relevance
“…Indeed, population-based studies looking at single markers or combinations of a limited number of PD risk markers have reported low PPVs, on the order of a few percent, up to a maximum of 10%-25%. 9,10 Higher PPVs of 40% of risk markers have only been achieved in enriched cohorts with a high a priory risk for PD such as hyposmic individuals or AUC, area under the curve; FU, follow-up; LR, likelihood ratio; PD, Parkinson's disease; 95% CI, 95% confidence interval. As outlined by the MDS task force, 4 pretest probability for prodromal PD is based solely on estimated age-specific disease prevalence.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, population-based studies looking at single markers or combinations of a limited number of PD risk markers have reported low PPVs, on the order of a few percent, up to a maximum of 10%-25%. 9,10 Higher PPVs of 40% of risk markers have only been achieved in enriched cohorts with a high a priory risk for PD such as hyposmic individuals or AUC, area under the curve; FU, follow-up; LR, likelihood ratio; PD, Parkinson's disease; 95% CI, 95% confidence interval. As outlined by the MDS task force, 4 pretest probability for prodromal PD is based solely on estimated age-specific disease prevalence.…”
Section: Discussionmentioning
confidence: 98%
“…Olfaction testing was performed using the 12-item smell identification test from Sniffin’ Sticks (SS-12; Burghart Messtechnik, Wedel, Germany) 21. Hyposmia was considered to be present if less than 9 of 12 smells were correctly identified 14 21. Colour vision was assessed using the Farnsworth-Munsell 100-Hue test (Torso-Verlag e.K., Wertheim, Germany); age-related 95% percentiles of error scores obtained in a normal population were used as a cut-off value for indicating disturbed colour vision 22.…”
Section: Methodsmentioning
confidence: 99%
“…Because few of these symptoms are specific to PD, such research may require simultaneous measurements of multiple NMS in large prospective studies and lengthy follow-up. While such research efforts are currently under way, for example, in the Prospective Evaluation of Risk Factors for Idiopathic Parkinson's Syndrome Study 39 and the Parkinson At-Risk Syndrome Study, 40 careful examinations on NMS among patients with de novo PD may be a costeffective approach to search for specific NMS or combinations of NMS that can best differentiate patients with PD from controls. Our regression analysis showed that only a few NMS measures in combination could effectively differentiate patients with PD from controls.…”
Section: 6mentioning
confidence: 99%